Soil investigations in Inglefield Land, Greenland. - Tedrow, J. C. F. (Meddelelser om Grønland, 1970)
During 1966, pedologic studies were conducted in Inglefield Land, Northwest Greenland (c. 78°31’ N, 70°55’ W) . Climate is typical of the high arctic with the July temperature approximating 40° F and the annual precipitation approximating 2 to 6 inches of water. The area has a desert appearance with most of the landscape free of vascular plants. Narrow swales and meadows, however, tend to be wet and covered with a continuous vegetative mat. The Archean basement complex is capped with Paleozoic rocks consisting of conglomerate, sandstone, shale, dolomite and limestone, together with a few intrusions of diabase. In the study area there is evidence of 3 glacial stages with the earliest ice probably reaching Rensselaer Bugt and beyond. A buried organic layer in a glacio fluvial terrace yielded a C-14 date of 20,800 yr. B.P. Six genetic soils or soil conditions are recognized: (1) Polar Desert soils, (2) Arctic Brown soils, (3) Tundra soils, (4) soils of the Hummocky Ground, (5) soils of the Polar Desert-Tundra interjacence, and (6) bedrock and boulder fields. Mechanical, mineralogical, and chemical analyses of the soils, including micromorphology, are given. Desert pavement and secondary carbonates form extensively in the welldrained sites. Laboratory data as well as field observations confirm a desert-like type of soil formation. Salts effloresce on certain soils during the rainless periods. Percent base saturation of the exchange complex is relatively high thoughout the area. Organic matter content approximates the 1 pet. level in the Polar Desert soils but increases in the wet positions. Many soil grains show allogenic clay coatings. Slight alteration of some feldspar was noted, but for the most part minerals are freshappearing. Some iron-stained aggregates have formed in the Polar Desert soils. Chemical composition of a number of native plants is given.